Morphology and morphosyntax of the adjective in the Gezer-Armana letters - Westhuizen, J. P. Van der (Journal for semitics, 2003)
Gezer-Amama letters were written in a Peripheral Akkadian (PA)dialect and the Gezer letters in a Western Peripheral Akkadian (WPA) dialect. Within this framework the morphology of the adjective in the Gezer letters was compared and thereafter the same procedure to the morphosyntax of the adjective in the Gezer letters was followed. The letters to be considered as being from Gezer are all addressed to the king of Egypt.